0
$\begingroup$

I am using the following definition:

  • Def.: let $E_1,...,E_p$ $p$-vector subspaces of $V$, $E_1+E_2+...+E_p$ is direct sum, $E_1+E_2+...+E_p \doteq E_1\oplus E_2 \oplus ... \oplus E_p$, if $$\forall e_1 \in E, e_2 \in E_2,...,e_p \in E_P (e_1+e_2+...+e_p=0_V \to e_1=e_2=...=e_p=0_V)$$

and I must to proof:

  • Prop.: let $E_1,...,E_p$ $p$-vector subspaces of $V$, then: $$\sum_{i=1}^pE_i \doteq \bigoplus_{i=1}^p E_i \leftrightarrow \forall i\in \{1,...,p\}(E_i \cap \sum_{t \in \{1,...,p\}-\{i\}}E_t=\{0\})$$

  • Proof: I thought (by induction), for $p=2$ I have $E_1,E_2$ $2$-vector subspaces of $V$, and I must to proof $$ E_1+E_2 \doteq E_1 \oplus E_2 \leftrightarrow \forall i \in \{1,2\}(E_i \cap \sum_{t \in \{1,2\}-\{i\}}E_t=\{0\})$$ but $\forall i \in \{1,2\}(E_i \cap \sum_{t \in \{1,2\}-\{i\}}E_t=\{0\})$ means $E_1 \cap E_2=\{0\} \wedge E_2 \cap E_1=\{0\}$ and it is true by CLIC and because $\cap$ is commutative; I must to proof ($p\to p+1$) $$[\sum_{i=1}^pE_i \doteq \bigoplus_{i=1}^p E_i \leftrightarrow \forall i\in \{1,...,p\}(E_i \cap \sum_{t \in \{1,...,p\}-\{i\}}E_t=\{0\})]\to [\sum_{i=1}^{p+1}E_i \doteq \bigoplus_{i=1}^{p+1} E_i \leftrightarrow \forall i\in \{1,...,p+1\}(E_i \cap \sum_{t \in \{1,...,p+1\}-\{i\}}E_t=\{0\})]$$ But I don't know to continue, I am confused...mmmm How can I do?

$\endgroup$
  • 1
    $\begingroup$ Unfortunately, induction won't work here. $\endgroup$ – DiffeoR Feb 26 '14 at 14:30
  • $\begingroup$ @DiffeoR, ah ok.. by contradiction? $\endgroup$ – mle Feb 26 '14 at 14:32
  • 1
    $\begingroup$ Yes ! that's the way to do. All the best. $\endgroup$ – DiffeoR Feb 26 '14 at 14:34
4
$\begingroup$
  • Proof of $\bf\leftarrow$

Let $e_i\in E_i$ such that $$e_1+e_2+\cdots+e_n=0$$ so forall $i$ we have $$e_i=-\sum_{j\ne i} e_j\in E_i \cap \sum_{j \in \{1,...,n\}-\{i\}}E_j=\{0\}$$

  • Proof of $\bf\rightarrow$ (by contraposition)

If there's $i$ such that $$E_i \cap \sum_{j \in \{1,...,n\}-\{i\}}E_j\ne\{0\}$$ so let $x\ne0$ in this intersection hence $$x=e_i=\sum_{j\ne i} e_j$$ so $$e_i-\sum_{j\ne i} e_j=0$$ but $$e_i\ne0$$ and this means that $E_1+E_2+...+E_p$ isn't a direct sum.QED.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Two proofs in one! Nice! $\endgroup$ – amWhy Feb 27 '14 at 13:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.